Florida Blueberry Leaf Disease Guide - Douglas A. Phillips; Norma C. Flor; Philip F. Harmon (EDIS)
Southern highbush blueberry (SHB) cultivars are commercially grown throughout much of Florida, in both deciduous and evergreen production systems. In both systems, leaves can be damaged by many factors including environmental conditions, chemical applications, insects, and diseases. This new 12-page publication of the UF/IFAS Plant Pathology Department includes basic information to assist growers in determining 1) the likely cause (fungal, viral, algal, or bacterial) of leaf symptoms, 2) when specific leaf spots are likely to occur, 3) characteristic symptoms of common leaf problems, and 4) some of the management options that are available. Written by Douglas A. Phillips, Norma C. Flor, and Philip F. Harmon. http://edis.ifas.ufl.edu/pp348